IMPLEMENTASI KEBIJAKAN PENEMPATAN TANSMIGRASI PADA UNIT PEMUKIMAN TRANSMIGRASI LEMBAN TONGOA KECAMATAN PALOLOKABUPATEN SIGI - Todengko, Efraim (Katalogis, 2015)
This study aims to determine and explain how the placement policy implementation transmigration Transmigration Settlement Unit (UPT) Lemban Tongoa Sigi. This type of research is used qualitative selection techniques and the number of informants purposively selected informants 8 people. Date was collected through interviews, observation and documentation. Date analysis techniques through the stages of editing the data, categorization, interpretation of the meaning of date and conclusion. The theory used models implementasike policy and Van Horn Van Metter with aspectsÂ aspects that objective and policy standards, resources, disposition, characteristic of the implementing agencies, communication between the organization and implementation of activities, and conditions economic, social and political. The results showed that the aspect of Standards and Objectives penyelenggaraaan transmigration policy in UPT. Lemban Tongoa, has not demonstrated the achievement of goals, Aspect Resources funds / charges provided to carry out the selection and placement of transmigration is still inadequate, Aspect Disposition of the Implementing policies there is a sense of disappointment surrounding communities transmigration settlement Lemban Tongoa on the implementation of the selection of prospective migrants and placement are less accommodating people around, Aspect Communication between organizations in the implementation of the deployment policy of transmigration in UPT Lemban Tongoa has been executed, Aspect Characteristics Agent Implementing policies is still a paternalistic nature that can not be ruled out in the implementation of policies and Environmental Aspects: Economic, Social and Political in policy implementation are factors that influence the official interest policy implementation.